Implementasi Business Intelligence Untuk Menganalisis Data Destinasi Wisata di Indonesia Menggunakan Platform Tableau - Diana Fitri Lessy; Lita Astri Pramesti; Rafli Erlangga; Muhammad Rafly Al Fattah Zain; Firman Noor Hasan (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2022)
Tourist destinations are one of the main choices that can be made in spare time. Indonesia is a country that is famous for its beauty, so it attracts many tourists to visit. The purpose of this study focuses on visualizing tourist destination data in Indonesia by implementing Business Intelligence to display places, prices and ratings from five cities in Indonesia. The method of this research is to process a dataset of tourist destinations in Indonesia from www.kaggle.com using the Tableau platform. The results of this study are in the form of reports in the form of dashboards such as places, prices and ratings from five cities in Indonesia which are used in the decision-making process to make it easier and more systematic. The data display from the results of the analysis that has been carried out produces an attractive and interactive dashboard provided by Tableau.